Changing Borders, Stable Attitudes: The National and European Identity Before and After the Most Recent EU Enlargements - Sergiu Gherghina (Romanian Journal of European Affairs)
This article investigates whether changes occur in the national and European identities of the citizens from the old and new Member States following the 2004 and 2007 enlargements. Complementary, it seeks to identify the major attitudinal determinants of national and European identities for the EU citizens. The analysis focuses on the 27 EU Member States and uses individual level data from the 2002-2009 Candidate Countries and Standard Eurobarometers. The descriptive statistics and multivariate quantitative analyses reveal that no relevant changes occur in the levels of national and European identities. The two types of identities coexist and are shaped at various levels. Their determinants appear to be quite stable over time, thus indicating no major alterations after the enlargement.